1999
DOI: 10.1177/08959374990130011901
|View full text |Cite
|
Sign up to set email alerts
|

Implant Surfaces and Interface Processes

Abstract: The past decades and current R&D of biomaterials and medical implants show some general trends. One major trend is an increased degree of functionalization of the material surface, better to meet the demands of the biological host system. While the biomaterials of the past and those in current use are essentially bulk materials (metals, ceramics, polymers) or special compounds (bioglasses), possibly with some additional coating (e.g., hydroxyapatite), the current R&D on surface modifications points toward much… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
201
0
7

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(213 citation statements)
references
References 46 publications
5
201
0
7
Order By: Relevance
“…[1] The adsorption of proteins in this early stage strongly influences the biocompatibility of a material. [2] During the adsorption process, the proteins may undergo conformational changes. [3] In some cases the interaction between the surface of the biomaterial and proteins, such as osteointegration, promotes the integration of a biomaterial in the human body.…”
Section: Introductionmentioning
confidence: 99%
“…[1] The adsorption of proteins in this early stage strongly influences the biocompatibility of a material. [2] During the adsorption process, the proteins may undergo conformational changes. [3] In some cases the interaction between the surface of the biomaterial and proteins, such as osteointegration, promotes the integration of a biomaterial in the human body.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, the cement topography showed some R a and R m values of about 5 and 30 lm, respectively. Previous studies have shown that surface topography features at the cell scale affect the behaviour of cells [26]. For example, looking at the BMSC behaviour on rough titanium surfaces compared to smoother ones with identical surface chemistry, Deligianni [27] found an increased cell adhesion, a slightly higher proliferation and similar ALP activity on rougher surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of the peptide at the surface (C s ) can be expressed as (2) where q is the excess amount of peptide per unit area adsorbed on the surface compared to that under bulk solution conditions (i.e., C b ) and δ is the thickness of the adsorbed layer.…”
Section: Iib Model Developmentmentioning
confidence: 99%